2006
DOI: 10.1002/jcp.20655
|View full text |Cite
|
Sign up to set email alerts
|

Human subcutaneous adipose cells support complete differentiation but not self‐renewal of hematopoietic progenitors

Abstract: Adipose tissue is now considered as an endocrine organ implicated in energy regulation, inflammation and immune response, and as a source of multipotent cells with a broad range of differentiation capacities. Some of these cells are of a mesenchymal type which can -- like their bone marrow (BM) counterpart -- support hematopoiesis, since in a previous study we were able to reconstitute lethally irradiated mice by cells isolated from adipose tissue. In the present study, we established that cells derived from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 42 publications
3
63
0
2
Order By: Relevance
“…We have also found that WAT contains a full urea cycle 58 and a potentially active amino acid metabolism 14 . The results obtained, and a growing list of unique capabilities of WAT [59][60][61][62][63][64] has decided us to focus on the quantitative analysis of WAT metabolism. Thus, we checked these parameters against the known functional and morphologic differences of WAT sites [65][66][67] , and their modulation by sex and diet 14,68 , as well as, especially, the effects of metabolic syndrome 69,70 .…”
Section: Discussionmentioning
confidence: 99%
“…We have also found that WAT contains a full urea cycle 58 and a potentially active amino acid metabolism 14 . The results obtained, and a growing list of unique capabilities of WAT [59][60][61][62][63][64] has decided us to focus on the quantitative analysis of WAT metabolism. Thus, we checked these parameters against the known functional and morphologic differences of WAT sites [65][66][67] , and their modulation by sex and diet 14,68 , as well as, especially, the effects of metabolic syndrome 69,70 .…”
Section: Discussionmentioning
confidence: 99%
“…This is predominantly due to opposing findings of multiple studies. It was originally assumed that adipocytes were simply passive space fillers in the BM upon observing the turnover of red marrow to yellow marrow attributable to age [7]. Naveiras et al, however, identified a reduction in HSC number after comparing adipocyte-rich tail vertebrae marrow with that of adipocyte-free thoracic vertebrae and noted an accelerated recovery after BM ablation of genetically modified fatless mice [8].…”
Section: Introductionmentioning
confidence: 99%
“…Adipositler, kısmen GM-CSF ve G-CSF gibi büyüme faktörlerinin az üretilmesinden dolayı, farklılaşmamış stromal veya preadipocytic benzerlerine göre, in vitro olarak hematopoezi daha az desteklemektedir (Corre et al, 2006). Ayrıca adipoz doku, her biri, hematopoietik proliferasyonu engelleyen nöropilin-1'i (Belaid-Choucair et al, 2008), lipokalin 2'yi (Miharada et al, 2008;Yan et al, 2007), adiponektini ve tümör nekroz faktörünü-α (TNF-α) salgılamaktadır.…”
Section: Adipositlerunclassified